2019
DOI: 10.1093/sleep/zsz271
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sleep on a high-heat capacity mattress on sleep stages, EEG power spectra, cardiac interbeat intervals and body temperatures in healthy middle-aged men‡

Abstract: Study Objectives This study deals with the question whether a slow (non-disturbing) reduction of core body temperature (CBT) during sleep increases sleep stage N3 and EEG slow wave energy (SWE) and leads to a slowing of heart rate in humans. Participants Thirty-two healthy male subjects with a mean ± SD age 46 ± 4 years and body mass index 25.2 ± 1.8 kg/m2. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 35 publications
3
27
0
Order By: Relevance
“…While many studies report T abdomen as a measure of T proximal , we have recently demonstrated that T back was a good indicator of T proximal during sleep of school aged children ( 59 ). This corresponds with studies of adults, which report that conductive heat loss through the proximal back is critical for slow wave sleep and subjective sleep quality ( 60 , 61 ). Similarly, Lan et al ( 62 ) found that local cooling of T back was most effective in alleviating thermal stress in a warm environment.…”
Section: Thermoregulation and Sleepsupporting
confidence: 86%
See 1 more Smart Citation
“…While many studies report T abdomen as a measure of T proximal , we have recently demonstrated that T back was a good indicator of T proximal during sleep of school aged children ( 59 ). This corresponds with studies of adults, which report that conductive heat loss through the proximal back is critical for slow wave sleep and subjective sleep quality ( 60 , 61 ). Similarly, Lan et al ( 62 ) found that local cooling of T back was most effective in alleviating thermal stress in a warm environment.…”
Section: Thermoregulation and Sleepsupporting
confidence: 86%
“…In their review of thermal environment and sleep quality, Lan et al (70) found that an in-bed microclimate of around 30 • C was most consistently associated with thermoneutrality for the sleeping human body, with relatively small variation across seasons and change in ambient temperatures. Various studies in adults have shown that the microclimate can be determined and indeed manipulated by types of mattresses (60,61,(73)(74)(75), bed sheets (76), personal heating or cooling devices such as electric blankets or airflow devices (77)(78)(79)(80) and clothing worn during sleep (46,81). While environment conditions, bedding and the microclimate clearly influence body temperature and perspiration, there is limited research examining the thermal comfort of children within their normal sleeping environments.…”
Section: Thermal Comfort and Sleepmentioning
confidence: 99%
“…Other approaches to enhance cognition have included the use of pharmacological agents (e.g., GABA modulators or orexin receptor antagonists, see Herring et al 2020) to increase sleep spindle density (Mednick et al 2013) or the use of closedloop auditory stimulation of slow-wave activity and sleep spindles (Ngo et al 2013), albeit there is some debate whether the latter technique is able to reliably improve memory performance (Henin et al 2019). In addition, sleep impairment is also, importantly, amenable to cognitive behavioral therapies (Geiger-Brown et al 2015;Morin and Benca 2012) as well as environmental adjustments and interventions (Herberger et al 2019). In turn, a greater understanding of sleep in AD may render sleep readouts as valuable diagnostic tools to identify risk of developing the disease and/or disease stage, particularly when integrated with blood-based, CSF, or neuroimaging biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…An inappropriate sleep environment results in difficulty falling asleep and affects nap quality and recovery from fatigue, and subsequent sleepiness ( Okamoto, Mizuno & Okudaira, 1997 ; Okamoto-Mizuno et al, 1999 ). Several studies have scientifically assessed the effect of bedding on nocturnal sleep and physiological variables during sleep ( Chiba et al, 2018 ; Herberger et al, 2020 ; Yu et al, 2020 ); a few studies have also demonstrated the relationship between suitable napping and associated environmental factors. Zhao et al (2010) showed that napping in a chair with the trunk tilted forward 45° and the head resting on a unique pillow was not significantly different from a nap in a bed in terms of objective sleep variables; however, compared with no-napping individuals, subjective sleepiness and fatigue improved in both the chair and bed conditions.…”
Section: Introductionmentioning
confidence: 99%